Influence of electromagnetic radiation on resistance of semiconductor devices - Serkov, А. A.; Breslavets, V. S.; Breslavets, Yu. V.; Yakovenko, I. V. (Національний університет "Полтавська політехніка імені Юрія Кондратюка", 2023)
The subject matter is the processes of analysis and mechanisms of appearance of instabilities of natural vibrations of semiconductor structures., due to their interaction with flows of charged particles under the influence of external electromagnetic radiation. It is shown that the influence of pulsed electromagnetic radiation is accompanied by the appearance of currents in the conductive elements of products that are capable of exciting natural oscillations of semiconductor components and are the cause of failures of radio products. The aim is to develop the theory of collisionless damping of surface polaritons in the classical approximation, as well as to study the mechanisms of collisionless damping of surface plasmons at the boundaries of semiconductor components of radio products under conditions when the temperature of carriers of conducting solids is much lower than the plasmon energy (quantum approximation). The objectives are: a kinetic equation describing the change in the number of surface plasmons as a result of their interaction with conduction electrons; obtaining its solution, which determine the decrement of oscillations and the power of spontaneous emission of particles. The methods used are: a method of successive approximations for solving the kinetic equations of the charged particle flux - semiconductor structure system within the framework of the quantum approach, when the interaction of waves and particles is in the nature of random collisions and is described by the method of secondary quantization of the system (representation of occupation numbers). The following results are obtained: Expressions are obtained for the decrements of surface plasmons in the presence of an infinitely high and infinitely small potential barrier at the interface between media. A kinetic equation is obtained that describes the change in the number surface plasmons as a result of their interaction with conduction electrons; his decisions are given, which determine oscillation decrement. Expressions are obtained for the decrements of surface plasmons at presence of infinitely high and infinitely small potential barrier at the interface between A physical model of the occurrence of reversible failures (effects induced by electromagnetic radiation currents per volt - ampere characteristics of semiconductor devices). The ranges of parameters of the external electromagnetic radiation at which this physical model is realized. Conclusion. Calculated relations are obtained that relate the parameters of semi-conductor structures: the concentration of free carriers, permittivity, carrier temperature with the value oscillation decrement in the classical and quantum approximations. The comparative analysis of quantitative estimates of the increments of oscillation instabilities carried out in the work makes it possible to solve the problems of optimizing the operating characteristics of active devices in the microwave range. The results of the work can be used in the development of microwave devices designed to amplify, generate and convert electromagnetic oscillations in the millimeter and submillimeter ranges.

Предметом дослідження є процес аналізу та механізми появи нестійкостей власних коливань напівпровідникових структур, обумовлених їх взаємодією з потоками заряджених частинок в умовах впливу зовнішнього електромагнітного випромінювання. Показано, що вплив імпульсного електромагнітного випромінювання супроводжується виникненням струмів у провідних елементах виробів, здатних збуджувати власні коливання напівпровідникових комплектуючих та бути причиною відмов радіовиробів. Метою статті є розробка теорії беззіткувального згасання поверхневих поляритонів в класичному наближенні, а також дослідження механізмів беззіткувального згасання поверхневих плазмонів на межах напівпровідникових комплектуючих радіовиробів в умовах, коли температура носіїв твердих тіл набагато менше енергії плазмону (квантове наближення). Цілі такі: кінетичне рівняння, що описує зміну числа поверхневих плазмонів внаслідок їх взаємодії з електронами провідності; отримання його рішення, що визначають декремент коливань та потужність спонтанного випромінювання частинок. Методи, що застосовувались при дослідженні: метод послідовних наближень розв'язання кінетичних рівнянь системи потік заряджених частинок – напівпровідникова структура в рамках квантового підходу, коли взаємодія хвиль та частинок носить характер випадкових зіткнень та описується методом вторинного квантування системи (подання чисел заповнення). Отримано такі результати. Отримано вирази для декрементів поверхневих плазмонів за наявності нескінченно високого та нескінченно малого потенційного бар'єру на межі розділу середовищ. Отримано кінетичне рівняння, що описує зміну числа поверхневих плазмонів у результаті взаємодії з електронами провідності; наведено його рішення, що визначають декремент коливань. Отримано вирази для декрементів поверхневих плазмонів за наявності нескінченно високого та нескінченно малого потенційного бар'єру на межі розділу середовищ. Обґрунтовано фізичну модель виникнення оборотних відмов (вплив наведених електромагнітним випромінюванням струмів на вольт – амперні характеристики напівпровідникових приладів). Визначено області параметрів зовнішнього електромагнітного випромінювання, за яких реалізується дана фізична модель. Висновки. Отримано розрахункові співвідношення, що зв'язують параметри напівпровідникових структур: концентрацію вільних носіїв, діелектричну проникність, температуру носіїв з величиною декременту коливань у класичному та квантовому наближеннях. Проведений у роботі порівняльний аналіз кількісних оцінок інкрементів нестійкостей коливань дозволяє вирішувати завдання оптимізації робочих характеристик активних приладів НВЧ –діапазону. Результати роботи можуть бути використані при розробці приладів НВЧ – діапазону призначених для посилення, генерації та перетворення електромагнітних коливань міліметрового та субміліметрового діапазонів.
Вплив електромагнітного випромінювання на стійкість напівпровідникових приладів
Keywords: flux of charged particles; electromagnetic radiation; semiconductor structures; surface vibrations; increment oscillation instability; потік заряджених частинок; електромагнітне випромінювання; напівпровідникові структури; поверхневі коливання; інкремент нестійкості коливань